Dari Melodi Ke Nilai: Kesenian Musik Gendang Beleq dalam Membangun Nilai-Nilai Masyarakat Pulau Lombok - Aji, Wahyu Trisno; Subaidi (Lembaga Intelektual Muda Maluku, 2024)
This study aims to explain what the traditional music art of Gendang Beleq is and how this traditional art builds the values ​​of people's lives in Lombok. This study uses a qualitative method with a socio-cultural approach, using the Postmodern paradigm. This study uses documentation techniques by collecting primary and secondary data from library sources including books, journals, website articles, magazines, and others. In this study, the results of the study found that Gendang Beleq is a traditional music art from Lombok not only as entertainment, but also reflects the cultural richness and identity of the Sasak people. Used in traditional events such as weddings and circumcisions, this art has a historical role as a driving force for fighting spirit, religious as a spiritual medium, and philosophical in teaching the values ​​of perseverance and wisdom. In addition to strengthening social solidarity and teaching cooperation, Gendang Beleq also functions as an educational medium to preserve tradition. Although born from the past, this art remains relevant and is an important symbol in the lives of the Lombok people